Emotional Intelligence and Affective Pedagogy: Pillars for a Humanized Education in the Health Sciences - García, Fernanda Irene Gómez (PT. Riset Press International, 2026)
Emotional intelligence is an essential competency in the training of health sciences students, as it promotes psychological well-being, improves academic performance, and strengthens the doctor-patient relationship. Affective pedagogy, which incorporates emotions into the educational process, is a key strategy for developing this type of intelligence in the university setting. Through a narrative review of 27 articles, we analyzed the relationship between emotional intelligence and affective pedagogy as the basis for a humanized education for health sciences students. The results indicated that students with higher emotional intelligence manage their emotions better in challenging contexts, which positively impacts their learning and the healthcare they provide. Furthermore, emotionally competent teachers and the use of affective methodologies significantly contribute to the development of these skills in students. Emotional intelligence in higher education is crucial for training more empathetic, resilient, and effective healthcare professionals. This requires educational environments that integrate the emotional component into teaching.